AMAP1 as a negative-feedback regulator of nuclear factor-κB under inflammatory conditions - Tien, Dat Nguyen (Nature Publishing Group, 2014)
NF-κB is a major transcriptional factor regulating many cellular functions including inflammation; therefore, its appropriate control is of high importance. The detailed mechanism of its activation has been well characterized, but that of negative regulation is poorly understood. In this study, we showed AMAP1, an Arf-GTPase activating protein, as a negative feedback regulator for NF-κB by binding with IKKβ, an essential kinase in NF-κB signaling. Proteomics analysis identified AMAP1 as a binding protein with IKKβ. Overexpression of AMAP1 suppressed NF-κB activity by interfering the binding of IKKβ and NEMO, and deletion of AMAP1 augmented NF-κB activity. The activation of NF-κB induced translocation of AMAP1 to cytoplasm from cell membrane and nucleus, which resulted in augmented interaction of AMAP1 and IKKβ. These results demonstrated a novel role of AMAP1 as a negative feedback regulator of NF-κB, and presented it as a possible target for anti-inflammatory treatments.